Characteristics of DHA-rich masked tuna eye oil and its application in fortified lokum formulation: Characteristics of DHA-rich masked tuna eye oil and its application in fortified lokum formulation - Santosa, Zacky Arivaie; Suseno, Sugeng Heri; Trilaksani, Wini; Santoso, Joko; Ibrahim, Bustami (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
Tuna eye oil is a source of omega-3 fatty acids, particularly docosahexaenoic acid (DHA); however, its application in food products remains limited because of its strong fishy odor and high susceptibility to oxidation. This study aimed to determine the most effective masking treatment for tuna eye oil to reduce fishy odor and improve oxidative stability and sensory acceptance in fortified lokum. The study was conducted in three stages: (1) extraction of tuna eye oil using centrifugation, (2) oil masking with lemon or ginger oil at concentrations of 12.5, 25, and 37.5%, and (3) formulation of fortified lokum using the selected masked oil. The extracted oil exhibited a free fatty acid (FFA) content of 0.42%, peroxide value (PV) of 7.44 meq/kg, anisidine value (AnV) of 9.98 meq/kg, and total oxidation (TOTOX) value of 24.84 meq/kg. Masking with lemon oil or ginger oil at 37.5% reduced oxidation parameters (FFA 0.12–0.28%; PV 4.49–6.61 meq/kg; p-AnV 3.08–3.75 meq/kg; TOTOX 12.06–16.96 meq/kg), enhanced antioxidant activity (IC₅₀ 140.76–166.41), and preserved the fatty acid profile, with DHA accounting for 29–30% of the total fatty acids. Fortification of lokum with masked tuna eye oil increased fat, EPA, and DHA levels, accompanied by measurable reductions in hardness and chewiness. Overall, masking tuna eye oil with 37.5 % %lemon and ginger oils effectively improved oxidative stability, with lemon oil showing the most balanced performance in terms of oxidation parameters, antioxidant activity, and sensory acceptance of fortified lokum.